Crude glycerol-mediated liquefaction of empty fruit bunches saccharification residues for preparation of biopolyurethane - Lee, Ju-Hee; Lee, Jae Hoon; Kim, Duk-Ki; Park, Chang-Ho; Yu, Ju-Hyun; Lee, Eun Yeol (Journal of industrial and engineering chemistry (Seoul, Korea), 2016)
•Empty fruit bunches residue was liquefied to prepare biopolyol using crude glycerol.•Hydroxyl number of the biopolyol was 1649.3mg KOH/g.•The biomass conversion at the optimal conditions was 71.3%.•The biopolyol was a suitable monomer for biopolyurethane synthesis. In order to utilize lignin residue from the pretreatment of empty fruit bunch (EFB) and crude glycerol from biodiesel production, lignin residue was solvothermally liquefied using crude glycerol to produce lignol. The optimal liquefaction conditions for lignol production were determined to be 10% biomass loading, 5% acid loading, a liquefaction temperature of 170°C, and a liquefaction time of 120min. The biomass conversion at the optimal conditions was 47.9%. The lignols possess hydroxyl number of 1649.3mg KOH/g and acid number of 8.4mg KOH/g. Fourier transform infrared spectroscopy revealed that the lignol was suitable for biopolyurethane synthesis.